Chemical Study and Biological Activity Evaluation of Two Azorean Macroalgae:Ulva rigida and Gelidium microdon - Madalena Silva (2013)
The green macroalga Ulva rigida C. Agardh (Chlorophyta) and the red macroalga Gelidium microdon Kützing (Rhodophyta), collected from the Azorean archipelago, were investigated for their secondary metabolites and their in vitro growth inhibitory effect on three human tumor cell lines: MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lung cancer) and A375-C5 (melanoma), as well as for their antifungal and antibacterial activities. The methanol extract of U. rigida furnished isofucosterol (1), 7(E)-3β-hydroxy-5α,6α-epoxymegastigmane (2) and (+)-dehydrovomifoliol (3) while the methanol extract of G. microdon yielded cholesterol (4) and lumichrome (5). The crude extracts of both macroalgae were found to be moderately active against the three cell lines whereas compound 1 showed a weak effect and compound 2 was inactive. The crude extracts of the two macroalgae were found to be moderately active against some fungi and bacteria while compounds 1 and 2 were inactive against all microorganisms tested.